PENGARUH ASIMETRI INFORMASI, UKURAN PERUSAHAAN, KEPEMILIKAN KELUARGA, PROFITABILITAS DAN LEVERAGE TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Indeks Kompas 100 yang Terdaftar di Bursa Efek Indonesia pada Tahun 2015) - M Beril; Azwir Azwir; Alfiati Alfiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the effect of Information Asymmetry, Size Company, Family Ownership, Profitability and Leverage to Earnings Management on Index Kompas 100 Companies listed in Indonesian Stock Exchange in 2015. The population was Index Kompas 100 Companies Listed in Indonesian Stock Exchange in 2015. Samples were taken by using purposive sampling method, where the kompas 100 companies that have complete data needed for the study period and the financial statements in the rupiah currency. Design research is hypothesis testing, where the sampleis composed of 48 companies. Processing data using multiple linier regression with SPSS 17.0. The results showed that the information asymmetry, family ownership and leverage does not affect to earnings management, while size company and profitability affect to earnings management. The coefficient of determination by five variables in this study affect the dependent variable by 14,6%, while 85,4% are influenced by other variables that are not described in this study.Keywords: Information Asymmetry, Size Company, Family Ownership, Profitability, Leverage, Earnings Management